TERORISME ATAS NAMA AGAMA - Wahyu Misbach; M. Mahdi Alatas (Institut Agama Islam Depok Al-Karimiyah Sawangan Depok, 2022)
Terrorism is still an interesting crime to talk about today. Not only because of the losses it generates, but because this term always refers to the same group, namely Islam. The WTC tragedy in 2001 became the gateway to history to embed terrorism slogans in the body of Islam. Until now, this is still a hot topic to be thrown by the media to the general public, as if to convince everyone that Islam is terrorism. This action seems to be agreed upon by the Muslims themselves. Disputes within the body of Islam due to the plurality of interpretations, give birth to people who have excessive fanaticism towards a group. From here then born disbelief, which they assume as a form of loyalty to a group, and opposition to thoughts that are opposite or different from their group. The thing to note that loyalty is limited to what is natural is justified. However, when that loyalty turns into a struggle for the right to life, as well as intimidations that lead to all actions that harm other people, both materially and non-materially, it is enough for the public to call it an act of terrorism.